Structural Inequalities and Minority Rights: Analysing the Formal Aspects in Context of Pakistan - Ali, Danish; Bano, Tehzeeb; Ehsan, Madiha (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
This study has investigated public perceptions regarding minorities and their rights and examined the legal framework of Pakistan in context of minority rights along with the gaps within the formal system that allow violations and exploitations against the minorities. The research explored the perceptions of both groups regarding religious minorities and minority rights in Pakistan. Content analysis was done comparing the constitution of Pakistan against the Universal Declaration of Human Rights. To collect primary data in-depth interviews of students from the majority religious group and students from minorities groups were conducted. The findings reflect the critical situation being faced by the minorities in Pakistan, due to significant gaps between theory and practice existing in the legal framework. The law protects the minority rights, and they are given all equal rights by the constitution, but the implementation phase seems and remains unfulfilled due to numerous societal and religious factors influencing the formal system. It is recommended to device  inclusive polices to bring equality.